Reactivity and mechanisms of hydridic hydrogen of B–H in ammonia borane towards acetic acids: the ammonia B-monoacyloxy boranes. (18th May 2021) - Li, Huizhen; Li, Yunhui; Kang, Jiaxin; Fan, Lin; Yang, Qiuyu; Li, Shujun; Rahman, Abdul; Chen, Daqi
Abstract : B-monoacyloxy boranes are first obtained by moderate reactions of ammonia borane with acetic acids. Abstract : Non-classical acid–base neutralization reactions of ammonia borane (NH3 ·BH3, AB) with acetic acids are moderate, affected by strengths of acetic acid and its chloro derivatives, and concentrations and ratios of reactants. The experiment results indicate that only one hydridic hydrogen of B–H in AB is substituted and fortunately, four ammonia B-monoacyloxy boranes (NH3 ·BH2 OOCR, R = CH n Cl3− n, n = 0–3) are prepared. Two single crystals of 2NH3 BH2 OOCCH2 Cl·C12 H24 O6 and 2NH3 BH2 OOCCHCl2 ·C12 H24 O6 were obtained and analyzed first. Theoretical calculations demonstrated that these reactions are two-step elimination-addition process that takes advantage of the formation of dihydrogen bonds (DHBs) and hydrogen bonds (HBs), and aminoborane (NH2 BH2, AoB) is identified as the key intermediate.